Day-to-day intrapersonal variability in mobility patterns and association with perceived stress: A cross-sectional study using GPS from 122 individuals in three European cities. (September 2022) - Olsen, Jonathan R.; Nicholls, Natalie; Caryl, Fiona; Mendoza, Juan Orjuela; Panis, Luc Int; Dons, Evi; Laeremans, Michelle; Standaert, Arnout; Lee, Duncan; Avila-Palencia, Ione; de Nazelle, Audrey; Nieuwenhuijsen, Mark; et al.
Abstract: Many aspects of our life are related to our mobility patterns and individuals can exhibit strong tendencies towards routine in their daily lives. Intrapersonal day-to-day variability in mobility patterns has been associated with mental health outcomes. The study aims were: (a) calculate intrapersonal day-to-day variability in mobility metrics for three cities; (b) explore interpersonal variability in mobility metrics by sex, season and city, and (c) describe intrapersonal variability in mobility and their association with perceived stress. Data came from the Physical Activity through Sustainable Transport Approaches (PASTA) project, 122 eligible adults wore location measurement devices over 7-consecutive days, on three occasions during 2015 (Antwerp: 41, Barcelona: 41, London: 40). Participants completed the Short Form Perceived Stress Scale (PSS-4). Day-to-day variability in mobility was explored via six mobility metrics using distance of GPS point from home (meters:m), distance travelled between consecutive GPS points (m) and energy expenditure (metabolic equivalents:METs) of each GPS point collected (n = 3, 372, 919). A Kruskal-Wallis H test determined whether the median daily mobility metrics differed by city, sex and season. Variance in correlation quantified day-to-day intrapersonal variability in mobility. Levene's tests or Kruskal-Wallis tests were applied to assess intrapersonal variability in mobility and perceived stress. There were differences in daily distance travelled, maximum distance from home and METS between individuals by sex, season and, for proportion of time at home also, by city. Intrapersonal variability across all mobility metrics were highly correlated; individuals had daily routines and largely stuck to them. We did not observe any association between stress and mobility. Individuals are habitual in their daily mobility patterns. This is useful for estimating environmental exposures and in fuelling simulation studies. Highlights: Many aspects of our daily life are related to our mobility patterns and individuals can exhibit tendencies towards routine. Day-to-day variability in mobility was explored via six mobility metrics calculated from GPS data (n = . 3, 372, 919). Individuals were habitual in their daily mobility patterns. There were differences in intrapersonal mobility patterns by sex, season and by city. We did not observe any association between stress and mobility.